(untitled) (Revista Científica Integrada, 2025)
Objective: To report the experience of using playful strategies in promoting health among preschoolers, from the perspective of a Family Health resident nurse. Method: This is an experiential report conducted in two municipal early childhood education centers in a capital city in northeastern Brazil, from July 2024 to July 2025. Data were obtained through the resident’s field diary, capturing subjective impressions of the experiences. The activities followed a structured sequence consisting of three stages: welcoming, development, and conclusion. Results: Activities were carried out on the following themes: personal hygiene, oral health, healthy eating, promotion of a culture of peace, and dengue prevention. Final Considerations: These experiences contributed to the enhancement of professional practice in the areas of planning, development of playful resources, and implementation of health promotion actions for children.